The Importance of Hematological Parameters in Acute Respiratory Viral Infections in Children - L. A. Alekseeva; O. M. Ibragimova; I. V. Babachenko; T. V. Bessonova; N. N. Golovacheva (Журнал инфектологии)
Hematological studies are basic and mandatory in diagnostics and laboratory monitoring of infectious diseases, which led to their inclusion in the modern standards of laboratory examinations of children. Assessment of hematological parameters used for the provisional differential diagnosis of viral or bacterial nature of the disease. For research currently being used increasingly Hematology analyzers, which allows to facilitate and standardize the results. In this paper a comparison and differences hematological parameters practically healthy children and children with respiratory infections. Identified some changes in indicators of haemogram depending on the etiology and character of the clinical course of the disease. On the basis of the leukocyte formula defined leukocyte indices of intoxication and illustrates their importance in assessing the severity of the infection process.